2017
DOI: 10.1002/jrs.5110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new spectral signatures associated with dengue virus infected sera

Abstract: In a quest to use Raman spectroscopy as an optical diagnostic tool, we recorded Raman spectra of 32 dengue virus (DENV)-infected and 28 healthy sera samples in the near-infrared spectral range (540 to 1700 cm 1 ) using laser at 785 nm as the excitation source. We observed clear differences in the Raman spectra of DENV-infected sera as compared with those of healthy individuals. Here, as a result of our study, we report 12 unique Raman bands associated with DENV-infected sera that are not reported earlier. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Raman spectra of healthy and diseased blood plasma samples were acquired directly from the sample surface by placing its quantity of ~20 μL in a semispherical cavity of 5 mm in diameter and 5 mm deep, which was made on the surface of clean aluminum block. This sample holder was used because being metal, it does not produce Raman scattering and it radiates any heat if produced due to the focusing of laser on the sample 16 . The sample was placed under the microscope RSM‐785 coupled with Raman system Peak Seeker PRO‐785 (Agiltron, USA) for the acquisition of spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Raman spectra of healthy and diseased blood plasma samples were acquired directly from the sample surface by placing its quantity of ~20 μL in a semispherical cavity of 5 mm in diameter and 5 mm deep, which was made on the surface of clean aluminum block. This sample holder was used because being metal, it does not produce Raman scattering and it radiates any heat if produced due to the focusing of laser on the sample 16 . The sample was placed under the microscope RSM‐785 coupled with Raman system Peak Seeker PRO‐785 (Agiltron, USA) for the acquisition of spectra.…”
Section: Methodsmentioning
confidence: 99%
“…From the sample surface, ten Raman spectra were recorded by shining a laser power of 80 mW for an integration time of 10 s. Laser power was optimized carefully to avoid photodegradation. 31,32 Laser power was optimized in our last publication for serum samples. 31 Raman spectra were recorded with four laser powers at 40, 60, 80, and 100 mW.…”
Section: Methodsmentioning
confidence: 99%
“…31,32 Laser power was optimized in our last publication for serum samples. 31 Raman spectra were recorded with four laser powers at 40, 60, 80, and 100 mW. These spectra were found to be completely overlapping in spectral bands and linearly rising in intensity.…”
Section: Methodsmentioning
confidence: 99%
“…They reported 12 unique Raman bands associated with DENV‐infected sera that were not reported earlier. They concluded that these 12 Raman bands have the potential to be used as biomarkers for optical diagnosis of DENV infection . Antwi‐Boasiako et al described a bioconjugated graphene oxide‐based Raman probe for selective identification of SKBR3 breast cancer cells.…”
Section: Biosciencesmentioning
confidence: 99%
“…They concluded that these 12 Raman bands have the potential to be used as biomarkers for optical diagnosis of DENV infection. [59] Antwi-Boasiako et al described a bioconjugated graphene oxide-based Raman probe for selective identification of SKBR3 breast cancer cells. Their experimental results open up a possibility of new label-free Raman scattering assays for the reliable diagnosis of cancer cell lines by monitoring the "turn-off" of the Raman signal from a bio-graphene-oxide nanostructure.…”
Section: Medical and Biomedical Applications Tissues Plants And mentioning
confidence: 99%